2014
DOI: 10.1152/ajpheart.00312.2014
|View full text |Cite
|
Sign up to set email alerts
|

Exercise-mediated vasodilation in human obesity and metabolic syndrome: effect of acute ascorbic acid infusion

Abstract: We tested the hypothesis that infusion of ascorbic acid (AA), a potent antioxidant, would alter vasodilator responses to exercise in human obesity and metabolic syndrome (MetSyn). Forearm blood flow (FBF, Doppler ultrasound) was measured in lean, obese, and MetSyn adults (n = 39, 32 ± 2 yr). A brachial artery catheter was inserted for blood pressure monitoring and local infusion of AA. FBF was measured during dynamic handgrip exercise (15% maximal effort) with and without AA infusion. To account for group diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 37 publications
1
14
0
Order By: Relevance
“…As noted above, we have not observed large group differences in measures of vascular function in young obese humans or adults with metabolic syndrome (31, 33, 34). However, recent data from our group suggest unique phenotypes exist within groups of obese individuals which appear to drive impairments in subclinical measures of vascular function.…”
Section: Introductionsupporting
confidence: 66%
See 4 more Smart Citations
“…As noted above, we have not observed large group differences in measures of vascular function in young obese humans or adults with metabolic syndrome (31, 33, 34). However, recent data from our group suggest unique phenotypes exist within groups of obese individuals which appear to drive impairments in subclinical measures of vascular function.…”
Section: Introductionsupporting
confidence: 66%
“…Based on our work in resting humans (35), we hypothesized blood flow responses to acute exercise would be reduced in human obesity and/or metabolic syndrome. Surprisingly, and in direct contrast to data from animals, we have consistently found that young obese individuals and/or individuals with metabolic syndrome do not exhibit impairments in whole limb blood flow responses to acute exercise, and under certain conditions blood flow responses may actually be higher when compared to non-obese control subjects [Figure 3, (31, 33, 34)]. These data are not only in contrast with the majority of animal work, but also disagree with previous work conducted in humans (17, 27).…”
Section: Introductionmentioning
confidence: 60%
See 3 more Smart Citations